Role models influence on young adults purchase intentions and behaviors - Chung, Yen Nee. (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study replicates portions of Martin & Bush (2000) in a Malaysian consumers' context. intended to determine role models influence 011 young adults purchase intentions and behavior. Moreover. it intends to examine whether parents (direct) Dr celebrities (vicarious) role models are more influential on young adults purchase intentions and behaviors. The scope of this study is limited to young adults who aged between 19 -25 years old. A total of 250 questionnaires were distributed to 250 respondents that \",ere selected from University of Malaysia Sarawak (UNII'v1AS). However, only 237 completed questionnaires have been utilized . The results or Simple Linear Regression showed that role models have significant intlucnce Oil young adults purchase intentions and behaviors. [Iowever, celebrities (vicarious) arc found to be more influential than parents (direct) role models in influencing young adults purchase intentions and behaviors. This studies suggested that both pnn:nts and celebrities role more have significant influence on young adults purchase intentions and behaviors. Additionally, other issues raised from this study include the issues of consumer socialization theory, social learning theory and the theory or stimulus-organ ism-response. From the discussions, this study also suggested that policy makers should take into account the importance of parents in instilling good moral in today's' young adults.